Teaching Pharmacy Undergraduate Students Inhaler Device Technique and Exploring Factors Affecting Maintenance of Technique - Mariam Toumas-Shehata; Mark Henricks; Ludmila Ovchinikova; Lorraine Smith; Sinthia Bosnic-Anticevich (Canadian Respiratory Journal)
Aim. To determine the effect of inhaler device technique education on the maintenance of the inhaler device technique of undergraduate pharmacy students over time and to determine the factors, if any, related to inhaler device technique maintenance in the academic setting. Methods. This study took the form of a prospective, unpaired samples repeated measures design. Participants had their inhaler technique assessed at baseline. Participants were then shown how to use an inhaler as a group. Participants then worked in pairs and took turns teaching and assessing each other on the correct inhaler technique using the 9-step checklist. Immediately following the delivery of the intervention, participants had their inhaler technique reassessed. All participants were then trained to mastery through individualised training. Twelve months following the collection of baseline data, all participants had their inhaler technique assessed and completed two questionnaires. Results. Following the delivery of the intervention, there was a significant increase in the proportion of participants with the correct inhaler technique when compared to baseline (11% to 61%, resp.). There was a significant reduction in the proportion of participants demonstrating the correct technique 12 months following training (28%). The strongest determinant of inhaler technique maintenance is experience with showing patients how to use their inhalers. Conclusion. Repeated training is essential to ensure that the technique is mastered and maintained, and consolidation of skills through exposure to train others may be most effective.